Autonomous weapons systems and international norms - Bode, Ingvild; Huelss, Hendrik (McGill-Queen's University Press, 2022)
"Autonomous weapons systems seem on the path of becoming accepted technologies of warfare. The weaponization of artificial intelligence raises questions about whether human beings will maintain control of the use of force. The notion of meaningful human control has become a focus of international debate on lethal autonomous weapons systems among members of the United Nations: many states have diverging ideas about various complex forms of human-machine interaction and the point at which human control stops being meaningful. In Autonomous Weapons Systems and International Norms Ingvild Bode and Hendrik Huelss present an innovative study of how testing, developing, and using weapons systems with autonomous features shapes ethical and legal norms, and how standards manifest and change in practice. Autonomous weapons systems are not a matter for the distant future - some autonomous features, such as in air defence systems, have been in use for decades. They have already incrementally changed use-of-force norms by setting emerging standards for what counts as meaningful human control. As UN discussions drag on with minimal progress, the trend towards autonomizing weapons systems continues. A thought-provoking and urgent book, Autonomous Weapons Systems and International Norms provides an in-depth analysis of the normative repercussions of weaponizing artificial intelligence."-- Provided by publisher.
Keywords: Autonomous weapons systems.; Autonomous weapons systems (International law); Autonomous weapons systems -- Moral and ethical aspects.; International relations.; Security, International.; Artificial intelligence -- Military applications.; Artificial intelligence -- Moral and ethical aspects.; Weapons systems -- Technological innovations.; Weapons systems -- Technological innovations -- Moral and ethical aspects.; Relations internationales.; Intelligence artificielle -- Applications militaires.; Intelligence artificielle -- Aspect moral.; Systèmes d'armes -- Innovations.; Systèmes d'armes -- Innovations -- Aspect moral.; Systèmes d'armes létales autonomes.; Systèmes d'armes létales autonomes (Droit international); Systèmes d'armes létales autonomes -- Aspect moral.; international relations.; POLITICAL SCIENCE / International Relations / General.; Artificial intelligence -- Military applications; Artificial intelligence -- Moral and ethical aspects; Autonomous weapons systems; International relations; Security, International; Weapons systems -- Technological innovations; AI.; Peace.; air defense system.; autonomy.; conflict.; constructivist.; disarmament.; human machine interaction.; international law.; killer robots.; non-governmental.; norm emergence.; policy.; public.; regulation.; relations.; research.; science.; security algorithms.; technology.; think tanks.; war.; weaponized artificial intelligence.; Electronic book.